Daredevil : yellow - Loeb, Jeph; Sale, Tim (Marvel Universe, 2025)
" In this retelling of the early career of The Man Without Fear, the Eisner Award-winning team of Jeph Loeb and Tim Sale have taken an inspiring action adventure story and blended it with a romantic comedy. The result is the heartwarming and heartbreaking story of two young people in love--Matthew Murdock and Karen Page"--Rear cover.